Implementation of Modal Domain Transmission Line Models in the ATP Software - Colqui, Jaimis Sajid Leon; Eraso, Luis Carlos Timana; Caballero, Pablo Torrez; Filho, Jose Pissolato; Kurokawa, Sergio [UNESP] (My University, 2022)
Electromagnetic Transients Program make extensive use of transmission line models for the simulation of electromagnetic transients. This paper proposes a circuit representation of the modal transformation, more specifically Clarke's matrix. The arrangement of ideal transformers we propose allows modal transformation to be directly implemented in software such as Alternative Transient Program-Electromagnetic Transients Program. We combined the proposed circuit with single-phase transmission line models that consider frequency independent and frequency dependent parameters to represent transposed three-phase transmission lines. The main advantage of the proposed approach is that it allows the implementation of new transmission line models without depending on models provided in applications. To show this capability, we included the frequency dependence of soil parameters in the simulations. Results show that the proposed model is accurate both in the frequency domain and in the time domain.
Keywords: Clarke transformation matrix; electromagnetic transients; EMT-Type programs; Transmission line model